1996
DOI: 10.2337/diab.45.8.1141
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of fatty Due to Gln269Pro Mutation in the Leptin Receptor (Lepr)

Abstract: The rat fatty (fa) mutation produces profound obesity of early onset caused by hyperphagia, defective nonshivering thermogenesis, and preferential deposition of energy into adipose tissue. Genetic mapping studies indicate that fa and diabetes (db) are homologous loci in the rat and mouse genomes, respectively. It has been shown that db alleles carry mutations in the Lepr (leptin receptor) gene. This paper describes a point mutation in the fatty allele of Lepr. A nucleotide substitution at position 880 (A-->C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(66 citation statements)
references
References 13 publications
3
59
0
4
Order By: Relevance
“…Zucker rats are a genetic model of leptin receptor deficiency [25], [26]. As previously reported, homozygous Zucker rats (LepR fa /LepR fa ), weighed significantly more than lean Zucker rats when fed on chow (p<0.01; Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Zucker rats are a genetic model of leptin receptor deficiency [25], [26]. As previously reported, homozygous Zucker rats (LepR fa /LepR fa ), weighed significantly more than lean Zucker rats when fed on chow (p<0.01; Fig.…”
Section: Resultssupporting
confidence: 60%
“…Zucker rats are completely insensitive to leptin as a result of a single amino acid substitution of a glutamine for a proline in the leptin receptor gene (Ob-R) [ 25 ], [ 29 ]. Zucker rats homozygous for the fa gene are morbidly obese and characterized by fat cell hypertrophy and hyperplasia [30], increased adipose tissue, lipoprotein lipase activity [31], hyperinsulinemia, hypertriglyceridemia, and hyperphagia [32] compared to their lean heterozygous counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…These animals are homozygous for the fatty (fa/fa) allele, have a mutation in the leptin receptor, and are obese and exhibit characteristics of human metabolic syndrome (Aleixandre de Artinano and Miguel Castro, 2009; Zucker, 1961). They become noticeably obese by the 3 rd to 5 th week after birth (Aleixandre de Artinano and Miguel Castro, 2009) and exhibit hyperphagia (Chua et al, 1996b). Food restriction normalizes body weight without affecting body composition and excessive body fat persists in these animals (Cleary et al, 1980).…”
Section: Rodent Models Of Obesity and Obesity Resistance: Sleep/wamentioning
confidence: 99%
“…The leptin receptor fatty gene ( Lepr fa ) is a recessive mutation that leads to leptin receptor deficiency, and homozygous animals ( fa/fa ) exhibit obesity and hyperphagia, in addition to insulin resistance and glucose intolerance [6]. Previous reports demonstrated that WBKDF rats have severe obesity and insulin resistance, both of which lead to developing T2DM [1, 11, 15, 16].…”
mentioning
confidence: 99%